trans-Bis(4-methoxythiophenolato-κS)bis(trimethylphosphine-κP)nickel(II) - Cao, Ruixia (International Union of Crystallography, 2008)
The title compound, [Ni(C(7)H(7)OS)(2)(C(3)H(9)P)(2)], was obtained as a product of the reaction of [NiMe(2)(PMe(3))(3)] with two molar equivalents of 4-methoxythiophenol in diethyl ether. The compound is stable in the air for several hours, but rapidly decomposes at room temperature in solution. The Ni atom displays a square-planar coordination with two P-donor atoms lying in trans positions. The benzene rings of the thiophenolate ligands are almost perpendicular to the square coordination plane, making dihedral angles of 80.43 (4) and 72.60 (4)°.